Successful neoadjuvant chemotherapy plus sintilimab for locally advanced cervical cancer: case series and review of the literature - Linlin Liu; Xianbo Deng; Shuang Guo; Shouhua Yang (BMC, 2023)
Abstract Background The locally advanced cervical cancer (LACC) of FIGO stage IB3-IIA2 is characterized by large local mass, poor prognosis and survival rate. Tumor response to neoadjuvant chemotherapy for LACC, utilized as a surrogate endpoint, is urgently needed to improve. Given that the antitumor immune response can be suppressed by programed death-1 axis, the treatment paradigm of neoadjuvant chemotherapy combined with immunotherapy has been explored as one of the prognostic treatments in a variety of solid carcinoma. So far, the application of sintilimab, a domestic immune checkpoint inhibitor, combined with neoadjuvant chemotherapy is still limited in LACC, especially in large lesions. Case description We present three postmenopausal women diagnosed with FIGO stage IB3-IIA2 cervical squamous cell carcinoma with lesions larger than 5 cm. Demographic, clinical, histopathological, laboratory and imaging data were record. At the completion of the neoadjuvant therapy with paclitaxel plus carboplatin combined with sintilimab, all patients underwent hysterectomy. After neoadjuvant treatment, a pathologic complete response in case 1 and partial responses in case 2 and case 3 were achieved, and neither patient showed any relapse during the follow-up period of 16 to 22 months. Conclusions This report provide evidence to support the combination of sintilimab with neoadjuvant chemotherapy in cervical cancer, which has yet to be validated in prospective studies. More clinical data are needed to verify the effectiveness of the combined regimens. This literature review also collected studies involving potential predictors of response to NACT and immunotherapy, which would be helpful in stratifying patients for future trials.